The Effect of Plant Growth Promoting Rhizobacteria and Arbuscular Mycorrhiza Fungi on the Growth and Essential Oil Yield of Patchouli (Pogostemon cablin Benth.) under Different Soil Water Content - Aini, Nurul; Kurniawan, Agus Prayitno; Maghfoer, Moch. Dawam; Yamika, Wiwin Sumiya Dwi; Kusuma, Restu Rizkyta (AGRIVITA Journal of Agricultural Science, 2026)
Patchouli produces essential oils, which are a crucial raw material for various industries, but its main limitation is its low essential oil content and yield. Water management, integrated with the use of beneficial microorganisms, serves as an alternative strategy. This study aims to evaluate the single and dual application of Plant Growth Promoting Rhizobacteria (PGPR) and Arbuscular Mycorrhizal Fungi (AMF) on the growth and essential oil production of patchouli under different Soil Water Content (SWC) levels. A two-factor factorial experiment was carried out in a randomized block design with three replications. The first factor was SWC levels (100, 75, 50, and 25% Field Capacity (FC)). The second factor was bioinoculant treatments (no inoculation (control), PGPR, AMF, and PGPR+AMF). The results showed that PGPR+AMF at various SWC levels improved growth and essential oil yield up to 96-190%. A reduction in growth was observed starting at 50% FC, as indicated by the number of leaves (>35%), leaf area (>44%), and plant dry weight (>32%). SWC at 75% FC resulted in 18% higher Water Use Efficiency (WUE) than 100% FC, while PGPR+AMF inoculation increased WUE up to 66%. In conclusion, maintaining SWC at 75% FC and treating the plant with PGPR+AMF inoculations optimized patchouli essential oil yield.